1994
DOI: 10.2134/agronj1994.00021962008600030017x
|View full text |Cite
|
Sign up to set email alerts
|

Wind Erosion Losses as Related to Plant Silhouette and Soil Cover

Abstract: Wind erosion adversely affects soils, plants, animals, equipment, the environment, and people. Wind erosion can be minimized or prevented by either standing residue or flat residue cover. Our objective was to develop mathematical relationships between these two crop residue properties and soil loss ratio (SLR: soil loss from protected soil/soil loss from flat, bare soil), for more accurate predictions of wind erosion soil losses. Therefore, from a previously reported wind tunnel study (wind tunnel 1.1 m high, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 4 publications
3
51
1
Order By: Relevance
“…The former value (74%) is similar to the efficiency of the 5-m-wide fallow vegetation windbreak (70%) described by Banzhaf et al (1992) and higher than the efficiency of surface mulching (46-64%, as mentioned earlier). This higher efficiency, compared with surface mulching, corresponded to the results in Chepil and Woodruff (1963), Siddoway et al (1965), and Bilbro and Fryrear (1994), which showed that the wind erosion controlling efficiency of standing residue was higher than that of flattened one. The trapping efficiency of the fallow band in this study (74% and 58% for annual incoming soil particles and COM, respectively) was lower than that of the 5-m-wide fallow land in Ikazaki et al (2011b,c) (93% and 97%, respectively).…”
supporting
confidence: 67%
“…The former value (74%) is similar to the efficiency of the 5-m-wide fallow vegetation windbreak (70%) described by Banzhaf et al (1992) and higher than the efficiency of surface mulching (46-64%, as mentioned earlier). This higher efficiency, compared with surface mulching, corresponded to the results in Chepil and Woodruff (1963), Siddoway et al (1965), and Bilbro and Fryrear (1994), which showed that the wind erosion controlling efficiency of standing residue was higher than that of flattened one. The trapping efficiency of the fallow band in this study (74% and 58% for annual incoming soil particles and COM, respectively) was lower than that of the 5-m-wide fallow land in Ikazaki et al (2011b,c) (93% and 97%, respectively).…”
supporting
confidence: 67%
“…It is successful in reducing erosion and in reducing the loss of water from fields by decreasing evaporation. The relationship between soil loss and vegetation cover (live or dead) is generally exponential: the soil loss ratio is at a maximum of 1 on a bare unprotected surface but decreases rapidly to a value of approximately 0.2 with 40% soil cover [72]. However, work in Sahelian Africa has shown that maintaining a crop residue cover of just 2% on a field reduces the potential wind erosion by at least a factor of three [73].…”
Section: Controlling Wind Erosion On Croplandmentioning
confidence: 99%
“…In most models, non-erodible surface cover includes coarse rock fragments and flat-lying plant residue. Generally, there is an exponential decrease in soil loss with increasing surface cover (Bilbro and Fryrear, 1995). Non-erodible surface cover can be determined using line transects (Laflen et al, 1981) or by counting points touching cover elements on a grid overlaid on a nadir-view photograph of the field.…”
Section: Field Surface Conditionsmentioning
confidence: 99%